2014
DOI: 10.1080/15568318.2014.893043
|View full text |Cite
|
Sign up to set email alerts
|

Future priorities for a climate-friendly transport: A European strategic research agenda toward 2030

Abstract: Research is a key factor for a successful reduction in greenhouse gas (GHG) emissions from transport. This paper summarizes the main results of REACT, a project co-financed by the European Commission, which aimed to develop a European Strategic Research Agenda for low GHG transport. A literature review and a multi-stage expert consultation process were used to map technological and non-technological research areas and evaluate them according to different criteria (i.e., GHG emissions reduction, costefficiency,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…These three 'pillars' are constantly addressed in the literature on sustainability and issues around establishing a balance between the pillars remains a subject of considerable debate [2,35]. To understand the full implications of a new technology on sustainable development clearly requires a range of studies that target these complexities.…”
Section: Sustainability: a Working Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…These three 'pillars' are constantly addressed in the literature on sustainability and issues around establishing a balance between the pillars remains a subject of considerable debate [2,35]. To understand the full implications of a new technology on sustainable development clearly requires a range of studies that target these complexities.…”
Section: Sustainability: a Working Definitionmentioning
confidence: 99%
“…There is an urgent need to find and develop alternative energy sources for stationary and mobility applications [1,2]. Climate change, local pollution, fossil fuel use and lack of energy security pose significant risks for people and ecosystems [3].…”
Section: Introductionmentioning
confidence: 99%
“…Research on transitions in the energy and mobility sectors has found that a paradigm shift to sustainable mobility has not yet taken place, and a more radical approach is needed to tackle climate change (Banister, 2008;Khalaj et al, 2020). Transport is a challenging sector to decarbonize due to its complexity, and how it intertwines with all aspects of our society (Luè et al, 2016). Transport accounts for 23 % of global energy-related emissions (IPCC, 2022), and this share is expected to rise to 50 % of the global emission by 2030 (Hickman & Banister, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The implication of this is that the end of life vehicles part will need to be monitored and managed so that these wastes do not constitute another burden to the environment. This concern is also being expressed in electrical and electronics equipment where plastic is now the source of components parts [14]. To broaden the sources of plastic waste, studies have shown that plastics have been excessively produced in the last 60 years, couple with the fact that their longevity in the environment cannot be ascertained as most literature [15].…”
Section: Introductionmentioning
confidence: 99%